Dry-Heat Resistance of Bacterial Spores Recovered from Mariner-Mars 1969 Spacecraft - Wardle, M. D. (1971)
The dry-heat resistances of 70 bacterial spore isolates recovered from Mariner-Mars 1969 spacecraft were determined and expressed as D values (decimal reduction times). Fifty per cent of the spore isolates had D values of 60 min or less at 125 C. Of organisms with D values greater than 60 min, four were selected for a study of the effect of sporulation medium and suspension menstruum on dry-heat resistance. Both sporulation medium and suspension menstruum were found to affect significantly the dry-heat resistance of the bacterial spores tested.